1997
DOI: 10.1099/00221287-143-4-1369
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the bet genes encoding glycine betaine synthesis in Sinorhizobium meliloti 102F34

Abstract: As a first step towards the elucidation of the molecular mechanisms responsible for the utilization of choline and glycine betaine (betaine) either as carbon and nitrogen sources or as osmoprotectants in Sinorhizobium meliloti, we selected a T n 5 mutant, LTS23-1020, which failed to grow on choline but grew on betaine. The mutant was deficient in choline dehydrogenase (CDH) activity, failed to oxidize [methyl-14C]choline to [methyl-I4C]betaine, and did not use choline, but still used betaine, as an osmoprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…The luteolin-induced osmotolerance could increase bacterial fitness and thus constitutes an advantage for its successful plant root colonization (Biondi et al 2009). The two major osmoprotection systems characterized in E. meliloti are represented by betaine-glycine (Mandon et al 2003;Le Rudulier et al 1984;Pocard et al 1997) and ectoine (Talibart et al 1994). In vitro expression studies Capela et al 2005;Roux et al 2014) revealed no evidences that the betaine system (betICBA operon) was induced by luteolin.…”
Section: Discussionmentioning
confidence: 99%
“…The luteolin-induced osmotolerance could increase bacterial fitness and thus constitutes an advantage for its successful plant root colonization (Biondi et al 2009). The two major osmoprotection systems characterized in E. meliloti are represented by betaine-glycine (Mandon et al 2003;Le Rudulier et al 1984;Pocard et al 1997) and ectoine (Talibart et al 1994). In vitro expression studies Capela et al 2005;Roux et al 2014) revealed no evidences that the betaine system (betICBA operon) was induced by luteolin.…”
Section: Discussionmentioning
confidence: 99%
“…The aldehyde dehydrogenase superfamily comprises seven enzymes of bacterial and plant origin with known involvement in the synthesis of the osmoprotectant glycine betaine from its precursor glycine betaine aldehyde. These are the BetB proteins from E. coli (13) and Rhizobium meliloti (41) and betaine aldehyde dehydrogenases from plants (Spinacia oleracea, Beta vulgaris, Atriplex hortensis, Sorghum bicolor, and Hordeum vulgare) involved in the cellular adaptation to salinity and drought (24,36,53,56,57). The B. subtilis enzyme exhibits 39% sequence identity to the BetB proteins from E. coli and R. meliloti.…”
Section: Vol 178 1996 Glycine Betaine Synthesis In B Subtilis 5123mentioning
confidence: 99%
“…1). The S. meliloti chromosome also encodes a betaine aldehyde dehydrogenase, as well as choline dehydrogenase, BetA (65). The pSymA BetI may be redundant with chromosomal SMC00095 (49).…”
Section: Stress Responsesmentioning
confidence: 99%